2005
DOI: 10.1037/0021-843x.114.3.706
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions and adhd in adults: Evidence for selective effects on ADHD symptom domains.

Abstract: Dual-process models of attention-deficit/hyperactivity disorder (ADHD) suggest that both executive functioning and regulatory functions (e.g., processing speed) are involved and that executive function weaknesses may be associated specifically with symptoms of inattention-disorganization but not hyperactivity-impulsivity. Adults aged 18-37 (105 with ADHD, 90 controls) completed a neuropsychological battery. The ADHD group had weaker performance than did the control group (p<.01) on both executive and speed mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
200
3
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(234 citation statements)
references
References 70 publications
25
200
3
6
Order By: Relevance
“…Results showed that the persistent inattentive group scored significantly lower than the persistent hyperactive group on measures of executive functions. Inattention was also associated with slower processing speed, and hyperactivity was associated with faster processing speed (Nigg et al, 2005). In a study that considered childhood inattention and hyperactivity/ impulsivity symptoms as separate predictors, the inattention symptoms were found to be predictive of substance use among adolescents with ADHD (Molina & Pelham, 2003).…”
Section: Considering the Effects Of Different Types Of Adhd Symptomsmentioning
confidence: 99%
“…Results showed that the persistent inattentive group scored significantly lower than the persistent hyperactive group on measures of executive functions. Inattention was also associated with slower processing speed, and hyperactivity was associated with faster processing speed (Nigg et al, 2005). In a study that considered childhood inattention and hyperactivity/ impulsivity symptoms as separate predictors, the inattention symptoms were found to be predictive of substance use among adolescents with ADHD (Molina & Pelham, 2003).…”
Section: Considering the Effects Of Different Types Of Adhd Symptomsmentioning
confidence: 99%
“…La selección de los sujetos en la fase de screening se realizó mediante el Cuestionario de Conducta de Conners para profesores en su versión abreviada. El objetivo de la aplicación de este cuestionario es la identifi cación de sujetos en los que se puede sospechar la presencia Nigg et al, 2005) para comparar los grupos con TDAH y el grupo de control en cuanto a la puntuación en todas las dimensiones de la escala BRIEF. La inclusión de esta covariante se justifi ca porque estimamos que una variación de 4 años (la edad de los niños en todos los grupos oscila entre los 9 y los 13 años) podía infl uir en la puntuación obtenida en la escala BRIEF.…”
Section: Procedimientounclassified
“…Many of the symptoms and difficulties the women experience are consistent with executive dysfunction and poor inhibitory control (see, for example, Barkley, 1997;Brown, 2009;Nigg et al, 2005), and with dysfunction of the motivation and reward circuits in the brain (Volkow et al, 2011). Procrastination and motivational difficulties hinder the women from taking full advantage of their academic and occupational skills, regardless of, for example, their high intelligence, because "there's no point in being smart if you can't work like a worker bee, like other people do.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…Executive and motivational dysfunction affect the regulation of cognitive processes involved in goal-directed behavior, and can manifest as poor time management, a tendency to easily get bored, procrastination, indecisiveness, disorganization, and dysregulation of attention, behavior, and emotions (Brown, 2009;Nigg et al, 2005;Nussbaum, 2012;Volkow et al, 2011). The participants struggle significantly with indecisiveness, for example, "I'll flip from one option to the other and drive myself and everybody else crazy," as well as with stress and feelings of unpredictability resulting from poor planning and structuring skills.…”
Section: Present Main Symptoms and Challengesmentioning
confidence: 99%